Innovative Technologies for Ensuring Railway Safety in Mudflow Emergencies - N. Ya. Makhkamov; S. S. Sulaymonov; Sh. Kh. Abdazimov (European Journal of Life Safety and Stability (2660-9630), 2022)
The article provides a theoretical analysis of the number and scale of risks of railways and their infrastructure passing through mountainous and foothill areas, the dependence of flood activity on these areas and processes, their spatial and temporal variation, and the development of emerging mudflows. Based on the developed scenarios, the development and installation of continuous local and space surveillance systems is being carried out to control system damage and the impact of floods caused by emergencies in the mountainous and foothill areas of the railway, as well as a sharp decrease in vulnerability to floods.